The Functional Role of Spontaneously Opening GABAA Receptors in Neural Transmission - O’Neill, Nathanael; Sylantyev, Sergiy (Frontiers in Molecular Neuroscience, 2019)
Ionotropic receptors of γ-aminobutyric acid (GABAARs) produce two forms of inhibitory signalling: phasic inhibition generated by rapid efflux of neurotransmitter GABA into the synaptic cleft with subsequent binding to GABAARs, and tonic inhibition generated by persistent activation of extrasynaptic and/or perisynaptic GABAARs by GABA continuously present in the extracellular space. It is widely accepted that phasic and tonic GABAergic inhibition are mediated by receptor groups of distinct subunit composition and modulated by different cytoplasmic mechanisms. Recently, however, it has been demonstrated that spontaneously opening GABAARs (s-GABAARs), which do not need GABA binding to enter an active state, make a significant input into tonic inhibitory signalling. Due to GABA-independent action mode, s-GABAARs promise new safer options for therapy of neural disorders (such as epilepsy) devoid of side effects connected to abnormal fluctuations of GABA concentration in the brain. However, despite the potentially important role of s-GABAARs in neural signalling, they still remain out of focus of neuroscience studies, to large extent due to technical difficulties in their experimental research. Here we summarize present data on s-GABAARs functional properties and experimental approaches that allow isolation of s-GABAARs effects from those of conventional (GABA-dependent) GABAARs.